Cutting-edge industrial technology of mining tool manufacturing - Savchenko, Iu.; Gurenko, A.; Naumenko, O. (Розробка родовищ, 2016)
Purpose. To conduct a comparative economic analysis of cermet alloys regeneration technology, to identify the most “environmentally friendly” and cost-effective processing of solid alloys waste. Methods. As a research technique, the present article considers analysis of current methods of solid tungsten cobalt alloys regeneration: pyro and hydro metallurgical, chemical (chlorine, zinc), thermochemical and the method which uses energy of blasting explosives. Findings. A comparative economic analysis of cermet alloys regeneration technologies was conducted. Originality. Fundamental way of shock wave treatment to stimulate destruction of powder product of any configuration in order to obtain a high quality powder for further formation, sintering and tool manufacturing of multiple use is demonstrated; ecologically friendly technology of hard alloys and cermet components of outdated military hardware and ammunition recycling has been developed. Practical implications. Industrial implementation of the developed technology allows to solve the following issues: – utilizing super hard metal and alloys scrap for subsequent regeneration, which ensures significant savings of strategic raw material; – the use of new technology, which excludes ineffective ways of scarce raw materials processing and manufacturing products satisfying international standards; – gradual reduction of import in favor of hard alloys cermet tools; – reduction and subsequent abandonment of strategic metals and alloys scrap export, shifting towards the export of ready products – powders and tools, which will significantly increase foreign currency earnings in the country.